26-Nor-D:A-friedooleanane triterpenes from Phyllanthus watsonii - Matsunaga, Shunyo; Tanaka, Reiko; Takaoka, Yoshikazu; In, Yasuko; Ishida, Toshimasa; Rahmani, Mawardi; M.Ismail, Hazar Bebe (Pergamon Press, 1992)
Two new unsaturated nor-triterpenes were isolated together with lupenyl palmitate, friedelin, epifriedelanol, glochidone, glochidonol, lupeol, lup-20(29)-en-1β,3β-diol, sitosterol and sitosterol-β-(d)-glucoside from the aerial parts of Phyllanthus watsonii, and their structures were established to be 26-nor-D:A-friedoolean-14-en-3-one and 26-nor-D:A-friedoolean-14-en-3β-ol, respectively, on the basis of chemical, spectral and single crystal X-ray analyses.